Patient education materials on pressure injury prevention in hospitals and health services in Victoria, Australia: Availability and content analysis. Issue 2 (18th December 2019) - Team, Victoria; Bouguettaya, Ayoub; Richards, Catelyn; Turnour, Louise; Jones, Angela; Teede, Helena; Weller, Carolina D.
Abstract: Pressure injuries (PIs) are a common quality indicator for hospital care, and preventing PIs often requires patient engagement; as such, Australian consensus research has recommended that high‐quality education materials be made to patients for PIs via hospital networks. The purpose of the present study was to assess the availability and accuracy of patient education materials on PIs in publicly available hospital websites in Victoria, Australia. Two independent coders assessed 212 websites for content on PI prevention and management, analysing availability and accuracy of PI definitions, risk factors, preventive strategies, referral, visual tools, consumer endorsement, information for family/carers, and translation on community languages. A greater proportion of hospitals did not have any patient education materials on PI prevention publicly available, with private hospitals (compared with public) and metropolitan hospitals (compared to rural) more likely to have materials available on their sites. The available materials contained accurate messages on PI defining characteristics and risk factors for PIs, although there was considerable variability on the availability of other information. Our findings suggest a significant deficit in the availability of educational materials for acute care patients and their families. There is a need for evidence‐based, consumer‐endorsed, uniform materials on all hospital websites to prevent PIs in acute care.